Effects of Soundpainting Training on Attention - Coşkuner, Sonat; Stalheim, Jostein (Journal of History Culture and Art Research, 2020)
In particular, the relationship between music and brain, which is the subject of research by neurologists and neuropsychologists, has started to attract the attention of musicians and educators in recent years. Musicians try to make sense of the music they do instinctively, while educators try to clarify how the relationship between music and brain reflects on education. In this study, the effects of Soundpainting education, which is a multi-disciplinary, live composing sign language for musicians, dancers, actors and visual artists, has been investigated. The study is an experimental study based on pretest-posttest model with experimental-control group. The study group is comprised of 3rd grade students studying in the Department of Music at the University of Norway Applied Science (Bergen). Sentences consisting of soundpainting syntax can be short and sometimes long. The long sentences pointed out by the Soundpainter require the performers to receive a high level of visual attention. As the visual attention was measured in this study, Victoria Stroop Attention Test was applied as a data collection tool. In the light of the data obtained in the study, it was concluded that there was no significant difference between the post-test results of the experimental and control groups, but that there was a significant difference between the results of the pre-test and post-tests of the experimental group.